2017
DOI: 10.25134/ieflj.v3i1.650
|View full text |Cite
|
Sign up to set email alerts
|

Improving Students� Factual Report Writing Skill by Using Content and Language Integrated Learning (Clil) Method

Abstract: Content and Language Integrated Learning (CLIL) seems worthy to investigate since it applies a language other than the student's mother tongue used as a medium of instruction. In this research, the researcher aims to portray two objectives, namely identifying whether CLIL method is effective to improve students' factual report writing skill, and examining students' attitude towards the implementation of this method. This research employs a quasi-experimental design through applying two instruments, namely test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…The research findings showed that the only communicative competence in which differences in favor of CLIL students were significant was spoken production and interaction. Almost the same with Cristina and Martínez (2017) and Kusmayadi and Suryana, (2017) analyzed the effect of CLIL on the writing competency of s students. This study was focused to analyze the writing product such as fluency, accuracy, grammatical complexity, and lexical complexity.…”
Section: Introductionmentioning
confidence: 81%
“…The research findings showed that the only communicative competence in which differences in favor of CLIL students were significant was spoken production and interaction. Almost the same with Cristina and Martínez (2017) and Kusmayadi and Suryana, (2017) analyzed the effect of CLIL on the writing competency of s students. This study was focused to analyze the writing product such as fluency, accuracy, grammatical complexity, and lexical complexity.…”
Section: Introductionmentioning
confidence: 81%
“…Meanwhile, several studies showed tangible evidence with regard to content knowledge and four language skills (listening, speaking, reading and writing). Kusmayadi & Suryana (2017) proved that there is a significant difference in the students' writing skill since CLIL approach was tailored to the experimental group. Students are able to improve both their writing skills and their understanding of the writing content.…”
Section: Suggestions For Clil Practice In Indonesian Efl Contextmentioning
confidence: 97%
“…Content can enrich, or reinforce language learning. Content can be drawn from many disciplines in a single lesson or unit (Curtain & Pesola, 1994;Kusmayadi & Suryana, 2017, Banegas, 2020. On the other hand, Content-Driven CLIL primarily focuses the teaching and learning on the subject content, and evaluation is based on students' knowledge of the content and not on language proficiency (Met, 1999;Nikula & Mård-Miettinen, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A language-driven CLIL Unit was elaborated based on the qualitative results and on theories by Met (1999), Coyle, Hood and Marsh (2010), Olsson (2010), Bentley (2010), and Kusmayadi and Suryana (2017). It was essential to divide the unit into single lessons considering Content-Compatible Language and Content-Obligatory language objectives (Bentley, 2010;Banegas, 2012).Seven lesson-plans were created, and each one of them took 5 class periods.…”
Section: Interventionmentioning
confidence: 99%